The nature of values and their place in human life and the world (Journal of Philosophy Culture and Political Science, 2018)
This article presents an analysis of the problem of values and considered insights, which became the basic methodology of research in the category of «value». Determining value is very important to recognize the nature of human nature and society. A certain unfolding phenomenon in the society itself is not transformed into value. The article says that it is valuable only as one element of a whole image of the world or of a particular socio-cultural community and the individual. The interaction of values is the relationship of the subjects of interaction, objects are carriers of values, values values and the values themselves. These elements are interlinked and they cannot stay outside of this close connection. In the issue of values, you may notice two such opposing views of the consent and reasoning. Only when familiarity with the concept of «values» offered by representatives of various axiological movements and schools, it is possible to notice the criticism on the current state of the theory of values. We can note a number of common qualities among the majority of the concepts and manifestations of values: a value is  characterized as having a value of the corresponding ideas for individuals or groups of individuals or as an object of precision (subject or abstract) of the aggregate of both; relative values formed two different existential and metaphysical opinion and on the basis of ethical opinion formed concepts of Good and Evil, it can be argued that in this framework, is defined and covered by a sufficient number of entities which can prove themselves, characterize the behavior of the person toward possession of the values.Key words: Values, benefits, personality, people, culture, globalization, transformation of values, society, public relations.